The Climatic Water Balance and Topography Control Spatial Patterns of Atmospheric Demand, Soil Moisture, and Shallow Subsurface Flow. Issue 3 (25th March 2019) - Hoylman, Zachary H.; Jencso, Kelsey G.; Hu, Jia; Holden, Zachary A.; Martin, Justin T.; Gardner, W. Payton
Abstract: Catchment hydrometeorology and the organization of shallow subsurface flow are key drivers of active contributing areas and streamflow generation. However, understanding how the climatic water balance and complex topography contribute to these processes from hillslope to catchment scales remains difficult. We compared time series of vapor pressure deficits and soil moisture to the climatic water balance and topographic variables across six zero‐order catchments in the Lubrecht Experimental Forest (Montana, USA). We then evaluated how local hydrometeorology (volumetric water content and atmospheric vapor pressure deficit) affected the spatial occurrence of shallow subsurface flow. Generalized linear mixed model analysis revealed significant, temporally stable (monthly and seasonal average) patterns of hydrometeorology that can be predicted by the topographic wetness index and the dynamic climatic water deficit (CWD = potential evapotranspiration − actual evapotranspiration). Intracatchment patterns were significantly correlated to the topographic wetness index, while intercatchment patterns were correlated to spatiotemporal variance in the CWD during each time period. Spatial patterns of shallow subsurface flow were related to the hydrometeorological conditions of the site. We observed persistent shallow subsurface flow in convergent hillslope positions, except when a catchment was positioned in locations with high CWDs (low elevations and southerly aspects). Alternatively, we observed persistent subsurface flow across all hillslope positions (even 70‐m upslope from the hollow) when catchments were positioned in locations with especially low CWDs (northerly aspects and high elevations). These results highlight the importance of considering the superposition of the catchment‐scale climatic water balance and hillslope‐scale topography when characterizing hydrometeorology and shallow subsurface flow dynamics. Key Points: The climatic water balance and hillslope topography control spatiotemporal patterns of soil moisture and vapor pressure deficit Hydrometeorology explains spatiotemporal patterns of shallow subsurface flow across catchments The topographic organization of hydrometeorology and shallow subsurface flow is most apparent in semiarid regions